Document Review: Journal Articles, Performance Evaluations, and Organizational Citizenship Terminology - Julie D. Conzelmann (Business Ethics and Leadership)
The purpose of conducting the document analysis was to visually compare various performance review documents with topical literature noting the exclusion of language that identifies and measures organizational citizenship behaviors among employees in formal performance evaluation processes. A document analysis consisted of reviewing 56 publicly accessible, recent, and random performance review documents and 30 peer-reviewed journal articles identifying terms related to organizational citizenship behaviors. The expectation was to support the argument that most publicly accessible organizational performance evaluation documents exclude any significant terms related to organizational citizenship behaviors exhibited by employees. Findings from the document review supported the research inquiry of exclusion of terms listed in historical literature generally related to organizational citizenship behaviors in current performance evaluations. The inclusion of terms related to organizational citizenship behaviors in literature was extremely high. Emerson’s social exchange theory provided the theoretical foundation for the research. Podsakoff’s organizational citizenship behavior research was the principle impetus for comparison of performance evaluations and current literature, focusing on related terms for organizational citizenship behaviors in the workplace. Implications are that the belief and feeling of employee value, as based on formal performance evaluations, requires organizational leaders to provide a document worthy of measuring all aspects of expected and unexpected work behaviors. This paper addresses a need for organizational leaders to revise formal performance evaluation documents to ensure altruistic and above and beyond citizenship behavior terms from the literature are also part of the reward and recognition process. Changes in the formal performance evaluation process are necessary for future organizational success.